POWER AND SIZE OF NORMAL DISTRIBUTION AND ITS APPLICATIONS - Budi Pratikno; Jajang Jajang; Setianingsih Setianingsih; Raden Sudarwo (Universitas Jenderal Soedirman, 2017)
. The research studied power and size of normal distribution and its applications on linear regression model. The power and size formulas are derived, and the unrestricted test (UT), restrcited test (RT) and pre-test test (PTT) are used. The recommendation of the test is given by choosing maximum power and minimum size, and also graphical analysis. The result showed that the power and size for large standard deviation () tend to be identical and flat. In simulation study, the graphs of the UT, RT, and PTT are still similar to the previous research (Pratikno, 2012), where the PTT tend to lie between UT and RT.